C1272F: a novel type 2A von Willebrand’s disease mutation in A1 domain; its clinical significance - Woods, Adriana Inés (2011)
Most mutations identified in 2A VWD patients are localized in the A2 domain, although missense substitutions have also been recognized in the A1 domain. We describe a novel heterozygous missense mutation in the A1 domain of VWF gene responsible for type 2A phenotype. Analysis of the complete exon 28 was carried out in a patient and his mother with life-long histories of moderate to severe bleeding and laboratory data of type 2A VWD. The analysis of exon 28 of VWF gene showed a 3815 G fi T transversion resulting in C1272F mutation. It is probably associated with a group I mechanism according to patients’ clinical symptoms, and, in the case of the propositus, the lack of clinical response to treatment with desmopressin. The mutation was not found in 100 normal alleles. This substitution affected the normal S–S bound between C1272 and C1458, which is involved in A1 loop structure, altering the normal multimerization and function of VWF. The VWFpp/VWF:Ag ratio in the propositus and his mother was >3, suggesting a shortened survival of VWF. We believe it is important to report the complete clinical phenotype corresponding to the new mutation to increase the knowledge in the clinical field.